Fertility-sparing robotic-assisted radical trachelectomy and bilateral pelvic lymphadenectomy in early-stage cervical cancer - Chuang, Linus T; Lerner, Dimitry L; Liu, Connie S; Nezhat, Farr R (Journal of minimally invasive gynecology, 2008)
A combined pelvic lymphadenectomy with radical vaginal trachelectomy is an alternative to radical hysterectomy in the treatment of young women with cervical cancer desiring fertility preservation. This technique requires advanced vaginal surgery skills not commonly acquired. In an attempt to simplify the procedure we preformed what we believe to be the first case of robotic-assisted radical trachelectomy. A 30-year-old woman, gravida 1, para 1, desiring fertility preservation was given the diagnosis of invasive adenocarcinoma on cervical cone excision. The patient was treated with robotic-assisted pelvic lymphadenectomy and radical trachelectomy. We hope robotic-assisted radical trachelectomy will become an option for select women with early-stage cervical cancer who desire fertility preservation.